Peran Lapas Dalam Penanggulangan Penyelundupan Narkotika Perspektif Maqasid Syariah (Studi Lapas Kelas II A Kendari) - Aswandi Aswandi; Muh Asrianto Zainal; Muhammad Iqbal (QAIMUDDIN: Journal of Constitutional Law Review, 2022)
Correctional institutions are a place of guidance for correctional prisoners or correctional inmates (WBP), so it is appropriate that negative things should not happen that can damage the image of the prison itself, such as smuggling narcotics into prisons. The purpose of this study is to find out the background of the occurrence of narcotics smuggling, and to find out the role of prisons in countering narcotics smuggling from a sharia maqasid perspective. This research is a qualitative research using empirical normative research methods that focus on library and field research with a legal and case approach. Data collection techniques using interview techniques, documentation and observation. Based on the results of the research conducted, it can be concluded that the background to the occurrence of narcotics smuggling in the Class II A prison in Kendari are; the first is the economic factor, the second is the addiction factor and the third is because the prison location is easy to access, the fourth is the lack of human resources (HR) for the prison officers and the fifth is the lack of prison security facilities and infrastructure. The roles and efforts made by the Kendari Class IIA Prison in overcoming narcotics smuggling by providing guidance both from a social and spiritual perspective, increasing security, conducting education both through socialization and legal counseling and installing jammers as signal nuisance and trackers installed in every room of prisoners. Maqasid sharia perspective on the role of class IIA Kendari prison in dealing with narcotics smuggling is in accordance with Maqasid sharia in the field of daruriyat or primary needs, namely; protect religion, soul, mind, and property.Keywords: Prisons, Countermeasures, Narcotics, Maqasid Syariah